Penerapan Metode MOORA dan LOPCOW Dalam Seleksi Penerimaan Guru Bimbel - Ari Sulistiyawati (Journal of Artificial Intelligence and Technology Information (JAITI), 2024)
The selection of the right tutor admission is important to ensure that each teacher has strong pedagogical competence, communication skills, and material understanding, as well as the ability to manage the classroom and motivate students. However, the selection of ideal teachers based on these criteria is often a challenge due to the limitations of objective and transparent assessment methods. The combination of MOORA and LOPCOW in multi-criteria decision-making offers a robust and objective approach to ranking alternatives based on relevant criteria. The combination of these two methods is expected to be able to provide more accurate, efficient, and in accordance with the needs of tutoring institutions in recruiting qualified teachers. This research aims to provide a comprehensive solution in the selection process, but also contributes to the development of a selection method based on multi-criteria analysis in the context of education. The ranking results show an alternative ranking for tutoring teacher admissions based on the scores obtained by each prospective teacher. From these results, Yusuf Hakim is ranked first with the highest score of 0.3715, which shows that he is the strongest candidate to be accepted. The second place was occupied by Siti Zahra with a score of 0.3635, followed by Intan Permata who had a score of 0.3622 in third place. From this data, it can be concluded that Yusuf Hakim is the most recommended candidate to be accepted as a tutor, while Fajar Pratama has the lowest score in this assessment.